Free tools and strategies for the generation of 3D finite element meshes: Modeling of the cardiac structures - Pavarino, E. [UNESP]; Neves, L. A. [UNESP]; MacHado, J. M. [UNESP]; De Godoy, M. F.; Shiyou, Y.; Momente, J. C. [UNESP]; Zafalon, G. F D [UNESP]; Pinto, A. R. [UNESP]; Valêncio, C. R. [UNESP] (Hindawi, 2013)
The Finite Element Method is a well-known technique, being extensively applied in different areas. Studies using the Finite Element Method (FEM) are targeted to improve cardiac ablation procedures. For such simulations, the finite element meshes should consider the size and histological features of the target structures. However, it is possible to verify that some methods or tools used to generate meshes of human body structures are still limited, due to nondetailed models, nontrivial preprocessing, or mainly limitation in the use condition. In this paper, alternatives are demonstrated to solid modeling and automatic generation of highly refined tetrahedral meshes, with quality compatible with other studies focused on mesh generation. The innovations presented here are strategies to integrate Open Source Software (OSS). The chosen techniques and strategies are presented and discussed, considering cardiac structures as a first application context. © 2013 E. Pavarino et al.
Keywords: 3-D finite elements; Application contexts; Automatic Generation; Cardiac structure; Finite element meshes; Histological features; Open Source Software; Tetrahedral meshes; Mesh generation; Finite element method